Characterization and Spinning Performance of Pineapple Leaf Fibers: An Economic and Sustainable Approach for Bangladesh. Issue 8 (3rd August 2021) - Jalil, Mohammad Abdul; Parvez, Md. Shohan; Siddika, Ayesha; Rahman, Md. Moshiur
ABSTRACT: The by-products of pineapple fruits such as stems and leaves are generally considered as agro-wastes, but these wastes can be used as raw materials for reinforced fibre, yarn and eventually in fabric formation. Unlike PALF, Jute is a bast fibre and one of the main cash crops of Bangladesh, which has already proven as a versatile fibre. In this study, the spinning performance of PALF such as fineness, bundle strength, breaking tenacity and breaking elongation properties have been studied and compared with jute. It showed that the physical and structural characteristics of PALF were similar to jute fibre, even in some cases PALF is better. Another study was done in which it was found that surface characteristics like color strength (K/S value), whiteness, yellowness, and brightness signifies that the PALF yarn is almost similar in comparison with jute yarn. Besides, Pineapple Leaf Fibres contained relatively greater diameter compared with that for jute fibre and consequently, the quality ratio value of yarn for PALF was much smaller than that of jute yarn. Finally, a comparative decision is made; that the use of PALF can be a sustainable replacement toward an economy based agricultural solution for Bangladesh.